Modeling of Shrinkage, Rehydration and Textural Changes for Food Structural Analysis: A Review. Issue 2 (20th February 2014) - Parthasarathi, S.; Anandharamakrishnan, C.
Abstract Food processing is a unique method to create a structure that has been imparted by nature. The food‐processing industries are still facing some technological challenges like structural changes, appearance and simultaneous heat and mass transfer phenomena. Mathematical modeling and computer simulations of food systems can provide the distinctive insight of the food structure apart from the some critical examinations, which are not possible by experimental analysis. Moreover, the conventional experimental design optimization procedure involves time‐consuming expensive trial‐and‐error methods. This review describes the application of modeling techniques for predicting shrinkage during dehydration, textural changes and rehydration of porous food materials, etc. In addition, the challenges involved in modeling of food structure and product analysis, current limitations of commercial softwares, recent developments in this area and future applications are highlighted. Practical Applications The shrinkage of the food product is the change in volume of food material because of water loss during dehydration. Dried materials are either sold to customers as ready‐to‐use foods or for the production of powdery food materials. Rehydration is aimed at the restoration of the properties from the dehydrated food material. Texture contributes to the enjoyment and acceptance of food. Above three properties play an important role in determining the food characteristics. Physical, chemical and structural changes during the process determine the characteristics of the material. This review helps to apply different modeling techniques to understand the food microstructures.